(Counseling creativity of educational counselors in the General Directorate of Education in Kirkuk Governorate) - Kanaan, Wafa; Daly, Hussam Hussein (Journal of Tikrit University for Humanities, 2022)
As a result of the changes that have occurred in societies from a social point of view, And technology, the pressures increased and the problems intensified and their sources diversified, which increased the suffering of the person of the current century, and then his specialized professional assistance became in need of the counselor to think about the counselor’s problems and methods of solving and treating them outside the traditional box of counseling work. Educational counseling aims to help the student in drawing and defining plans And its educational and educational programs that are commensurate with his capabilities, abilities, preparations, interests, goals and ambitions, and dealing with academic problems that may encounter him, such as academic delays, slow learning and difficulties, so that the guide seeks to provide appropriate counseling services and good educational care for students (Moses, 2016: 9), guiding creativity enters Within the meaning of change, its beginning is a new idea aimed at Finding or improving a process that is being applied in order to provide certain services to the public in a better way (Al-Wazir, 2020: 18-19). Recognizing the level: 1 - Counseling creativity of educational counselors in the General Directorate of Education in Kirkuk Governorate. 2- Counseling creativity of educational counselors according to the gender variable (male/female). 3- Counseling creativity of educational counselors according to the variable years of service. - Research results: 1- The educational counselors have a good level of counseling creativity. 2- There are statistically significant differences between males and females in the counseling creativity in favor of males. 3- There are no statistically significant differences between the years of service in the level of extension creativity. Recommendations: 1- Adopting the Thinking Education Program as an independent curriculum and using it in secondary schools and teacher institutes because of its importance in developing indicative creativity. 2- Holding training courses and seminars to train counselors on how to implement the training program, so that its results can be used to solve students’ problems. 3- Making the mentor the main focus in the educational process and giving him the greatest role in discussion and inquiry.